2006
DOI: 10.1021/jp056715b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structural Characterization of Se-Modified Carbon-Supported Ru Nanoparticles for the Oxygen Reduction Reaction

Abstract: This work is part of a continued research aimed at the understanding of the promoting role of Se in the enhancement of the electrocatalytic activity of Ru in the oxygen reduction reaction. The objective of this paper is to systematically investigate the transformation of Ru nanoparticles upon their modification with the increasing amounts of Se. The Se-modified Ru/C samples with Se:Ru ratio from 0 to 1 were prepared by reacting carbon-supported Ru nanoparticles with SeO2 followed by reductive annealing and cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
130
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(153 citation statements)
references
References 27 publications
(41 reference statements)
19
130
0
2
Order By: Relevance
“…The ORR activity of Se-modified Ru NPs in H 2 SO 4 was higher than that of clean and Se-modified Ru disk. Zaikovskii et al fabricated Se-modified Ru/C by reacting Ru/C NPs with SeO 2 followed by annealing [102]. They prepared RuSe/C with different Se coverage by tuning the ratio of Se/ Ru.…”
Section: Other Noble Metal-based Nanocompositesmentioning
confidence: 99%
“…The ORR activity of Se-modified Ru NPs in H 2 SO 4 was higher than that of clean and Se-modified Ru disk. Zaikovskii et al fabricated Se-modified Ru/C by reacting Ru/C NPs with SeO 2 followed by annealing [102]. They prepared RuSe/C with different Se coverage by tuning the ratio of Se/ Ru.…”
Section: Other Noble Metal-based Nanocompositesmentioning
confidence: 99%
“…They found that this reaction is controlled by surface Other typical drawbacks in the cathodes of direct methanol fuel cells are related with the adsorption of oxygen on the catalytic nanoparticles, the kinetics associated with the O-O cleavage, the crossover of methanol and the reduction of surface metal oxides once the oxygen has been transformed in water [56]. In this sense, significant progress has been achieved by researchers studying the ORR reaction on ruthenium chalcogenides [6,7,57], heat-treated macrocyclic compounds of transition metals [58][59][60], and palladium-based catalysts [8,61,62]. Regarding the catalyst supported on carbon materials different than carbon blacks, Zheng et al supported palladium nanoparticles on carbon nanofibers and activated carbons in order to determine the influence of the carbon support on the ORR [63].…”
Section: Carbon-supported Pd-alloysmentioning
confidence: 99%
“…The high cost of these devices comes from the use of platinum and platinum alloys for methanol oxidation and oxygen reduction, the electrochemical reactions performed on anode and cathode, respectively. Some possible alternatives focused in the use of low platinum contents have been studied [3], particularly in the case of the cathode, suggesting materials including heat treated transition metals macrocycles [4,5], ruthenium chalcogenides [6,7] and palladium alloys [7,8]. Particularly, replacement of platinum and its alloys in the anode require more investigation, being the best solution the use of non-platinum catalysts in alkaline electrolytes [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Trotz intensiver Untersuchungen an RuSe x -Katalysatoren konnte bisher keine eindeutige Schlussfolgerung über den Aufbau der katalytisch aktiven Oberfläche der RuSe xNanopartikel gezogen werden. [6][7][8][9] Genau dies ist aber als Voraussetzung für weitere Verbesserungen anzusehen.…”
Section: Gegenwärtig Markieren Platinkatalysatoren Den Stand Derunclassified